2019
DOI: 10.5751/ace-01472-140219
|View full text |Cite
|
Sign up to set email alerts
|

Postfledging survival of the Worthington's Marsh Wren (Cistothorus palustris griseus)

Abstract: The postfledging period of a passerine bird's life is increasingly recognized as an understudied component of songbird conservation, because the habitat needs of fledglings can differ from nesting adults and survivorship during this period can substantially affect population growth rates. We studied postfledging survival of the Worthington's Marsh Wren (Cistothorus palustris griseus), a state-listed salt marsh songbird subspecies in northeastern Florida, USA, during 2016-2017. Postfledging survival was low dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Both wren and sparrow nests were associated with taller vegetation and higher stem counts, and nesting wrens and wren fledglings used tall cordgrass more often than short cordgrass, though use of tall cordgrass in fledglings declined as they aged (Figure 6A). Habitat needs of birds can vary across life stages, yet wren fledglings generally stayed close to their natal territories (Cox et al 2019) and selected similar vegetation features to those of nesting adults. Consistent with our predictions, fledglings somewhat shifted away from tall, dense cordgrass as they aged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both wren and sparrow nests were associated with taller vegetation and higher stem counts, and nesting wrens and wren fledglings used tall cordgrass more often than short cordgrass, though use of tall cordgrass in fledglings declined as they aged (Figure 6A). Habitat needs of birds can vary across life stages, yet wren fledglings generally stayed close to their natal territories (Cox et al 2019) and selected similar vegetation features to those of nesting adults. Consistent with our predictions, fledglings somewhat shifted away from tall, dense cordgrass as they aged.…”
Section: Discussionmentioning
confidence: 99%
“…Daily survival of sparrow nests was not associated with any of these habitat features, but there was no way to test the effect of needlerush because we did not find any sparrow nests in needlerush despite extensive searching. Post‐fledging survival for wrens was positively associated with tall cordgrass and negatively associated with needlerush (Cox et al 2019), but again other factors such as weight at tagging had a stronger effect on daily survival. It is likely that we would also see similar patterns of survival and vegetation use by sparrow fledglings, though we were unable to test these assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…Predation by snakes was the leading cause of mortality for fledgling Bachman’s Sparrows in our study, when cause of mortality could be identified. Snakes can be the largest organismal clade predating fledgling songbirds (Suedkamp Wells et al 2007, Giovanni et al 2015, Lehman 2017, Young et al 2019) or just one of many clades contributing to predation events (Kershner et al 2004, Jackson 2010, Cox et al 2019). Although relatively few studies of survival of fledgling songbirds have been conducted in the southeastern United States, Lehman (2017) found that snakes accounted for over half of all known predations events on Golden‐winged Warblers ( Vermivora chrysoptera ) in the Cumberland Mountains of Tennessee.…”
Section: Discussionmentioning
confidence: 99%
“…Though data for our study were derived from 18 species in eight different locations, methodologies were consistent across studies, with only a few minor differences in field techniques [see SI Appendix, Table S1 for full species list and associated studies (18,27,28,(45)(46)(47)(48)(49)(50) for more details]. For each species, trained field assistants searched for and monitored nests across the breeding season by systematic searching and observing adult behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…Data Availability. Data for this research are available through previously published manuscripts, dissertations, and theses (18,27,28,(45)(46)(47)(48)(49)(50), and the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%